Cracking the Nut on LCME Standard 8.7: Innovations to Ensure Comparability Across Geographically Distributed Campuses. Issue 5 (20th October 2019) - Foster, Johanna H.; Byerley, Julie; Tarantino, Heather; Chuang, Alice; Pino, Joseph; Latessa, Robyn; Nagappan, Suresh; Monroe, Rasheeda; Gilliland, Kurt; Steiner, Beat; Beck Dallaghan, Gary L.
Abstract: Problem: A large state university in the southeastern United States and state Area Health Education Centers (AHEC) collaborated to establish branch campuses to increase clinical capacity for medical student education. Prior to formally becoming branch campuses, two AHEC sites had established innovative curricular structures different than the central campus. These sites worked with the central campus as clinical training sites. Upon becoming formal campuses, their unique clinical experiences were maintained. A third campus established a curricular structure identical to the central campus. Little exists in the literature regarding strategies that ensure comparability yet allow campuses to remain unique and innovative. Intervention: We implemented a balanced matrix organizational structure, well-defined communication plan, and newly developed tool to track comparability. A balanced matrix organization model framed the campus relationships. Adopting this model led to identifying reporting structures, developing multidirectional communication strategies, and the Campus Comparability Tool. Context: The UNC School of Medicine central campus is in Chapel Hill. All 192 students complete basic science course work on central campus. For required clinical rotations, approximately 140 students are assigned to the central campus, which includes rotations in Raleigh or Greensboro. The remaining students are assigned to Asheville (25–30), Charlotte (25–30), or Wilmington (5–7). Chapel Hill and Wilmington follow identical rotation structures, 16 weeks each of (a) combined surgery and adult inpatient experiences; (b) combined obstetrics/gynecology, psychiatry, and inpatient pediatrics; and (c) longitudinal clinical experiences in adult and pediatric medicine. Asheville offers an 8-month longitudinal integrated outpatient experience with discreet inpatient experiences in surgery and adult care. Charlotte offers a 6-month longitudinal integrated experiences and 6 months of block inpatient experiences. Aside from Charlotte and Raleigh, the other sites are urban but surrounded by rural counties. Chapel Hill is 221 miles from Asheville, 141 from Charlotte, and 156 from Wilmington. Outcome: Using the balanced matrix organization, various reporting structures and lines of communication ensured the educational objectives for students were clear on all campuses. The communication strategies facilitated developing consistent evaluation metrics across sites to compare educational experiences. Lessons Learned: The complexities of different healthcare systems becoming regional campuses require deliberate planning and understanding the culture of those sites. Recognizing how size and location of the organization affects communication, the central campus took the lead centralizing functions when appropriate. Adopting uniform educational technology has played an essential role in evaluating the comparability of core educational content on campuses delivering content in very distinct ways.